Induction of primary NY-ESO-1 immunity: CD8+ T lymphocyte and antibody responses in peptide-vaccinated patients with NY-ESO-1+ cancers - Jäger, Elke (The National Academy of Sciences, 2000)
Cancer–testis antigen NY-ESO-1 is one of the most immunogenic tumor antigens defined to date. Spontaneous humoral and CD8+ T-cell responses to NY-ESO-1 are detected in 40–50% of patients with advanced NY-ESO-1-expressing tumors. A clinical trial was initiated to study the immunological effects of intradermal vaccination with 3 HLA-A2-binding NY-ESO-1 peptides in 12 patients with metastatic NY-ESO-1-expressing cancers. Seven patients were NY-ESO-1 serum antibody negative, and five patients were NY-ESO-1 serum antibody positive at the outset of the study. Primary peptide-specific CD8+ T-cell reactions and delayed-type hypersensitivity responses were generated in four of seven NY-ESO-1 antibody-negative patients. Induction of a specific CD8+ T-cell response to NY-ESO-1 in immunized antibody-negative patients was associated with disease stabilization and objective regression of single metastases. NY-ESO-1 antibody-positive patients did not develop significant changes in baseline NY-ESO-1-specific T-cell reactivity. However, stabilization of disease and regression of individual metastases were observed in three of five immunized patients. These results demonstrate that primary NY-ESO-1-specific CD8+ T-cell responses can be induced by intradermal immunization with NY-ESO-1 peptides, and that immunization with NY-ESO-1 may have the potential to alter the natural course of NY-ESO-1-expressing tumors.